PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KEMAMPUAN KONEKSI DAN PEMECAHAN MASALAH MATEMATIS SERTA SELF REGULATED LEARNING SISWA - Kurniawan, Feri; Budi, Asep; Saepul Mustakim, Usep (Staisman Press, 2023)
The study is intended to examine the issue of increasing the capability of connection and mathematical problem solving and self regulated learning (SRL) students through the learning of contextual teaching and learning (CTL), in terms of overall student and Early Math Ability category (KAM) students (high, medium, low). The research method is the mix method range of embedded. The population in this study are all the students of SMK Nur Pandeglang and Human Samples randomly selected two classes, namely class X 2 TKJ as class experiments, and class X 1 of the control class as TKJ. Instruments in this research in the form of a test and non-test. 6 the question of mathematical ability test connection, and 4 the question of mathematical problem solving ability tests, while tests of non instrument in the form of the now self regulated learning, observation sheets, and interviews. The results of this research were: 1) increased ability of Mathematical connections students who learn learning Contextual Teaching and Learning (CTL) is better compared to conventional learning when are reviewed from tegori Early Mathematical Ability (KAM) students; 2) increased Mathematical problem solving abilities students who learn learning Contextual Teaching and Learning (CTL) is better compared to conventional learning when are reviewed from tegori Early Mathematical Ability (KAM) students; 3) self regulated learning students who learn learning Contextual Teaching and Learning (CTL) is better compared to conventional learning: 4) there is a relationship between the ability of problem-solving and mathematical connections assembled and self regulated learning.